Estudo de utilização de medicamentos por idosos brasileiros - Anderson Lourenco da Silva (2009)
Elderly have a different drug use pattern when they are compared to other age groups. Excessive diagnoses and medications have been observed in the elderly and as a result, polypharmacy and inappropriate medicines use. With the increase of drugs use, the expenses with health spent on pharmaceutical care also have progressive increase, which turns more difficult the treatment access. The aim of this study was to assess the drugs use profile of Brazilian retirees and pensioners, with 60 years old or more, who had received from the Social Security. Three thousand people were selected, by simple random sampling, to anational survey by post. Information was obtained by questionnaires with closed and precodified questions, except those related to the medicines used. The characteristics of population and the medicines were described and it was made an assessment of the social economic condition, health condition and health service utilization associated to medicines use and polypharmacy. 1025 people (34.2% of the sample) answered the survey, 58.8% of those were women. The average of age of these elderly was 70 ± 6.9 years old, 50.2% were between 60 and 69 years old, 25.7% had never studied and the median pension value received from Social Security was R$200.00. About health status, 26.0% considered it at least good, the chronic diseases prevalence was 95.3%, the elderly reported, on average, 3 illnesses, and almost 90% had visited the doctor at least once in the last 12 months. On the 15 days beforethe interview, the dugs use prevalence was 82.5%, 3918 medicines were used (average = 3.8; range = 0 to20), and 35.5% of the people used 5 or more medicines. The drugs most frequently used were those that act in the cardiovascular system (30.7%), nervous system (16.8%) and food and treat metabolic (15.0%). The prevalence of use of at least oneinappropriate medication was 38.0%. Age (> 70 years old), higher education, four or more diseases reported, fail to perform daily activities and six or more consultations made in thelast 12 months, were positively associated with the use of 5 or more drugs (p <0.05). The findings were similar to the observed in others national and international studies. The high prevalence of polypharmacy reinforces the necessity of a policy to promote the correct use ofmedication by the elderly and the pharmaceutical care to this subgroup must be a constant concern of health caregivers.